Building a policy-oriented research partnership for knowledge mobilization and knowledge transfer: The case of the Canadian metropolis project - John Shields; Bryan Evans (Administrative Sciences, 2012)
The aim of this paper is to examine government-university-community partnerships for knowledge mobilization (KM) and knowledge transfer (KT) in the area of immigration and settlement research using the illustrative case of the Canadian Metropolis Project. The Metropolis Project in Canada began in 1995 with the goal of enhancing policy-oriented research capacity for immigration and settlement and developing ways to better use this research in government decision-making. Core funding for this partnership was provided jointly by Citizenship Immigration Canada (CIC), a department of the Government of Canada and the primary social science granting agency, the Social Science and Humanities Research Council (SSHRC). As of 2012, and subsequent to three successful funding phases, the decision was made to end government and SSHRC core funding for this initiative, however, other non-governmental funding avenues are being explored. The longevity of this partnership and the conclusion of this specific initiative present an opportunity to reflect critically on the nature of such partnerships. This paper is an attempt to identify some of the key themes, issues and challenges related to research partnerships, KM and KT. Also, with the aid of an illustrative case, it aims to specify some of the possibilities and limitations of this kind of policy relevant knowledge mobilization. Special consideration will be placed on the context in which the demand for knowledge mobilization and knowledge transfer has emerged. This examination has considerable international relevance as the Canadian Metropolis Project offers the leading example of a research partnership in the field of immigration and settlement.
Keywords: 350; knowledge mobilization; knowledge transfer; research partnerships; public policy; community-based research; immigration and settlement policy; policy communities